A gramática no livro didático de língua inglesa: reflexões sobre as abordagens de ensino - Sales, Ana Sabrina de (Universidade Federal Rural do Semi-Árido, 2019)
The language teaching that we know nowadays is a result of many types of research and attempts to understand how the best way to do it effectively. Many of these researches have resulted in what we understand today as the theories that are the governing principles of language teaching which are known as approaches (RICHARDS; RODGERS, 2016). That way, based on the assumptions of these conceptions developed over time, each component of the language has its own way of being approached in the classroom. In this sense, knowing that grammar is one of the components that stands out most when it comes to teaching foreign languages and with the need to understand the approaches which are used to teach grammar content in English language textbooks of elementary school, this study aims to make a textbook analysis focusing only on activities involving grammar to identify in which approach to language teaching these activities are based. For that reason, with an analysis of a qualitative and interpretative nature and based on the theoretical contributions of Richards and Rodgers (1999; 2010), Harmer (2007), Brown (2000), Larsen-Freeman and Anderson (2011), Silveira (1999), Antunes (2010), Oliveira (2014;2015), among others who study theories about language study, we perform the analysis of the grammar activities present in the textbook Alive! of English for elementary school. The data showed that there is a certain predominance of activities based on the traditional/grammatical approach and in the communicative approach. Therefore, we recognize that a better understanding of the history of language teaching techniques and approaches, as well as the recognition of the characteristics relevant to each theory is necessary considering that having knowledge of the theories and how they are applied in the materials used in the daily lessons of foreign language classrooms, the teacher will be able to reflect on their practice in order to recognize the best way to act and thus achieve the objectives previously outlined.
Monografia
Keywords: Abordagem; Gramática; Material didático; Material didático; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS INGLESA